Collision response between deformable objects in game environments [electronic resource] - 211660 Saandilian Devadas (Skudai : Universiti Teknologi Malaysia, 2007)
Thesis (Sarjana Sains (Sains Komputer)) - Universiti Teknologi Malaysia, 2007